Experimental Measurements of Host Identity Protocol for Mobile Nodes' Networks - Ben Jemaa, Maher; Abid, Nahla; Laurent-Maknavicius, Maryline; Chaouchi, Hakima (Journal of Computer Systems, Networks, and Communications, 2009)
The role of Internet Protocol (IP) is becoming more and more problematic especially with the new requirements of mobility and multihoming. Host Identity protocol (HIP) defines a new protocol between the network and transport layers in order to provide a better management to those requirements. The protocol defines a new namespace based on cryptographic identifiers which enable the IP address roles dissociation. Those new identifiers identify hosts rather than IP addresses. Because HIP is a quite recent protocol, we propose to present an experimental evaluation of its basic characteristics.